From Policy to Pedagogy: A conceptual Comparative Analysis of EFL Curriculum Policies in Indonesia, China, and South Korea - Tari Agustin; Karina Septiani; Sukarno Sukarno (Journal of English Language and Education, 2026)
This study examined English as a Foreign Language (EFL) curriculum policies in Indonesia, China, and South Korea through a qualitative comparative analysis of official curriculum documents and relevant scholarly literature. Drawing on Language Policy Theory, Curriculum Development Theory, and Educational Change Theory, the study explored how each country conceptualized English language education through curriculum orientation, pedagogical direction, and assessment practices. The findings revealed both similarities and differences across the three contexts. Indonesia adopted a relatively flexible and learner-centered curriculum emphasizing communicative competence, learner autonomy, differentiated instruction, and contextualized learning through Kurikulum Merdeka. In contrast, China maintained a centralized and examination-oriented curriculum structure characterized by strong governmental regulation, curriculum standardization, and high-stakes assessment despite recent communicative reforms. Meanwhile, South Korea demonstrated a hybrid curriculum orientation that combined communicative language education, globalization agendas, and strong academic competitiveness. The study further found that EFL curriculum policy in Asia reflects ongoing negotiations among globalization, educational modernization, sociocultural priorities, and national educational goals. Moreover, curriculum reform did not automatically result in uniform classroom implementation because educational practices continued to be influenced by institutional support, teacher readiness, governance structures, and assessment culture. The study contributes to comparative education and language policy scholarship by providing a conceptual understanding of how different Asian governments construct English education through curriculum policy.